Mechanical Properties: Programing Performance of Silk Fibroin Materials by Controlled Nucleation (Adv. Funct. Mater. 48/2016). (December 2016) - Chen, Zhengwei; Zhang, Honghao; Lin, Zaifu; Lin, Youhui; van Esch, Jan H.; Liu, Xiang Yang
Abstract : On page 8978, Y. H. Lin, Y. Y. Liu, and co‐workers demonstrate a precise control over the nucleation process of silk materials with the aid of mono‐disperse colloidal particles. Manipulation of the mesoscopic silk structure toward a desired macroscopic performance is achieved. Future research on soft materials and flexible devices will profit from this possibility to modulate silk fibroin gelation.